Quantum chemical texts as part of pedagogical content - Ескендирова, Азиза; Корганбаева, Жанар; Шаяхметова, Айсулу; Нурмуханбетова, Нургуль (Pedagogy and Psychology, 2022)
This article shows the possibilities of creating high-quality pedagogical content to increase the level of information transfer from the learner to the student, i.e., such forms of pedagogical reflection, which are an important component of pedagogical activity. Pedagogical activity is not a direct influence of one person on another, but their direct interaction. Therefore, the pedagogical process is the object of pedagogical activity, and the student assumes the position of a subject of pedagogical activity from the object of influence. In the current environment, every teacher deals with the task of providing a better presentation of material to students. Considering this process in the higher segment of the educational system, makes it possible for university teachers, who teach exact and applied subjects to use a method of presentation based on the application of quantization of educational texts. The use of quantized educational texts to improve the quality of learning is justified by the good perception and successful assimilation of educational information by both students and teacher s to update professional knowledge in accordance with the requirements of the time. The article presents a more detailed analysis of the efficiency of quantization technology, which was conducted among the teaching faculty of Kokshetau University named after S. Ualikhanov.